1994
DOI: 10.1128/jcm.32.2.393-397.1994
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test and PCR for direct detection of Mycobacterium tuberculosis in clinical specimens

Abstract: The Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test (AMTD) is a direct specimen assay for the identification ofMycobacterium tuberculosis from respiratory samples. rRNA is amplified, and the product is detected with a specific chemiluminescent probe. We performed a retrospective evaluation of three separate respiratory specimens from each of 250 patients by using the AMTD and compared the results with those of microscopy, culturing, and a patient chart review. From the latter results, 198 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 21 publications
12
59
2
Order By: Relevance
“…In the future, PCR quantification of MTB RNA may bring about an improvement in diagnostic accuracy, because active expression of mRNA implies the existence of viable organisms and may imply active infection when present above a certain quantity. The first results of the isothermal enzymatic amplification of MTB rRNA (Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test) from the sputa of patients with a pulmonological diagnosis (10,12) could be evidence in favor of this argument. However, even this test system revealed a positive reaction in 3.5% (7 of 198) of culture-and clinically Tb-negative patients in a study by Miller and coworkers (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, PCR quantification of MTB RNA may bring about an improvement in diagnostic accuracy, because active expression of mRNA implies the existence of viable organisms and may imply active infection when present above a certain quantity. The first results of the isothermal enzymatic amplification of MTB rRNA (Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test) from the sputa of patients with a pulmonological diagnosis (10,12) could be evidence in favor of this argument. However, even this test system revealed a positive reaction in 3.5% (7 of 198) of culture-and clinically Tb-negative patients in a study by Miller and coworkers (12).…”
Section: Discussionmentioning
confidence: 99%
“…The first results of the isothermal enzymatic amplification of MTB rRNA (Gen-Probe Amplified Mycobacterium Tuberculosis Direct Test) from the sputa of patients with a pulmonological diagnosis (10,12) could be evidence in favor of this argument. However, even this test system revealed a positive reaction in 3.5% (7 of 198) of culture-and clinically Tb-negative patients in a study by Miller and coworkers (12). The group describes the case of a patient with a history of Tb but no actual signs of it.…”
Section: Discussionmentioning
confidence: 99%
“…PCR. Recently, with the development of PCR, a number of investigators have reported the detection of a specific sequence for M. tuberculosis directly in clinical specimens (33). Amplicor PCR has been reported to be 100% specific and 83.6% sensitive for pulmonary tuberculosis.…”
Section: Approaches Based On Molecular Biologymentioning
confidence: 99%
“…Several clinical investigations confirmed high sensitivities and specificities both for MTD test (ELLNER et al, 1988;ABE et d., 1993;JONAS et al, 1993;LOROCCO et al, 1993;BODMIIR et al, 1994;MILLER et al, 1994;PFYFFER et al, 1994) and Accuprobe M. Avium Complex test (DRAKE'. GONZALEZ and HANNA, 1987;KIEHN and EDWARDS, 1987;MUSIAI.…”
Section: Introductionmentioning
confidence: 88%